Exploration of the Most Frequent Cause of Retrohyaloid Hemorrhage in Adult Patients (Journal of Armed Forces Medical College, Bangladesh, 2026)
Background: Retrohyaloid hemorrhage usually occurs at the interface between the posterior hyaloid and inner limiting membrane (ILM). This usually leads to severe visual impairment because of their specific location for the macular region.Objective: To see the most frequent causes of retrohyaloid hemorrhage in adult patient.Methods: Twenty four eyes of 24 cases were evaluated in Combined Military Hospital Dhaka. Patients presented with sudden profound painless loss of vision with varieties of causative factors like constipation, coughing, pregnancy, uncontrolled diabetes, hypertension, blood disorders and strenuous exercise. Patient geographical data along with description of retrohyaloid hemorrhage were recorded in predefined data sheet.Results: Retrohyaloid haemorrhages were clinically diagnosed in 24 eyes of 24 patients (median age 32 years). Age limit were 05 years to 70 years. Best corrected visual acuity was grossly impaired in all patients because of involvement of central macular area. Among those, only two patients were presented with history of valsalva due to constipation and weight lifting. Eight (33.33%) patients were presented with retrohyaloid hemorrhage with uncontrolled diabetes with features of proliferative diabetic retinopathy among the detectable cases. Blood disorders were the cause of retrohyaloid hemorrhage in 4(16.17%) patients. One patient was presented with third pregnancy. Rest of the patients had no identifiable cause. Twenty eyes were treated with YAG Laser hyaloidotomy resulted in excellent visual recovery.Conclusion: Retrohyaloid hemorrhage often occur in a specific clinical context and can lead to severe visual impairment in adult patients. Though there are varieties of risk factor, uncontrolled diabetes with features of proliferative diabetic retinopathy is the significant frequent cause of retrohyaloid hemorrhage.JAFMC Bangladesh, Vol 21, No 1 (June) 2025:16-18